The Relationship Of Husband's Support And Exposure To Information Regarding The Use Of Intracinal Contraceptive Devices (IUD) - Wigunarti, Mirna (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2024)
Indonesia is a country with the 4th largest population in the world with a population growth rate of 1.49% per year. The Health Profile of Papua Province shows that IUD contraceptive users are still low (0.93%). This study aims to determine the relationship between husband's support and information exposure to the use of intrauterine contraceptive devices (IUD). This study used a cross sectional design. The research sample of 81 respondents were taken using a purposive sampling technique. Data collection instrument using a questionnaire. The results showed that there was a relationship between husband's support and IUD information exposure to IUD use at the Sentani Health Center. Husband's involvement needs to be increased to support mother's decision making in family planning. Access to information regarding family planning should not be limited to mothers as potential acceptors, but also conveyed to the husband.